Reliability modeling and planning of energy harvesting based on uncertainty theory - Zhe WANG; Taoshen LI; Jin YE; Zhihui GE; Min WU (Tongxin xuebao)
Energy harvesting network is a new form of computer networks.It can convert the environmental energy into usable electric energy,and supply the electrical energy as a primary or secondary power source to the electronic device for network communication.However,the energy harvesting process has great volatility and uncertainty,the traditional analytical method based on probability distribution function to describe the energy collection process can not accurately simulate the actual situation,resulting in higher depletion probability of nodes,then the reliability cannot be guaranteed as a result.For this,the energy harvesting reliability of energy harvesting nodes was defined,represented with the degree of normal operation,respectively set up the node reliability models with no battery and infinite battery.As an example for maximum node achievable rate,the uncertain multilevel programming model based on node reliability was put forward,then the network efficiency was improved under the premise of ensuring node reliability.An energy average allocation (EAA) algorithm was proposed and the upper bound of competitive ratio of the algorithm was proved theoretically.Finally,the actual wind power data was taken as an example to verify the feasibility and effectiveness of the proposed model and method.